Vortex-Driven Magnetospheric Heating in Primordial BlackHoles - Osmanov, Z. N.
The existence of a photon mass or an efficient accretion process might lead to an extremely high magnetic field. This, in turn, induces centrifugal acceleration, which parametrically triggers the excitation of Langmuir waves. In the final stage, through Landau damping, a significant fraction of the amplified electrostatic waves is converted into heat, warming the magnetosphere of primordial black holes.
Keywords: Astrophysics